Fenomena Penerapan Asuhan Kebidanan Holistik Islami dalam Mendukung Tumbuh Kembang Balita di Tempat Praktik Mandiri Bidan - Anita Yuliani; Nike Arta Puspitasari; Gita Kirana (Faletehan Health Journal, 2025)
The implementation of holistic Islamic midwifery care plays a significant role in supporting the growth and development of toddlers, particularly in independent midwifery practices. This study aims to identify and explore the application of holistic Islamic midwifery care and its impact in supporting toddler growth and development in independent midwifery practices. The research employed a mixed-methods approach with a convergent parallel design, involving 132 toddler’s mother and 3 midwives as respondents. Quantitative data were collected through questionnaires, while qualitative data were obtained through in-depth interviews. The results showed that 75.8% of mothers rated the midwifery services as "good," and 83.3% felt highly involved in their baby's care. The holistic Islamic approach, encompassing physical, mental, and spiritual dimensions, positively influenced mothers' understanding of their babies' health and increased their involvement in the care process. However, education regarding this approach needs to be strengthened, particularly in understanding its spiritual aspects. Overall, this study concludes that the application of holistic Islamic midwifery care supports toddler growth and development by enhancing the quality of baby care and increasing maternal involvement.